Computer modeling of electrical transmission lines under transient operating conditions using traveling wave theory (Damascus University Journal for engineering sciences, 2021)
Electrical power systems are studied through several methods, the most important of which is modeling & simulation, which are used as tools to represent these systems in a virtual environment. The most popular method is the representation of the system by a numerical (computer) model consisting of three components: algebraic and differential mathematical equations, solution algorithms, and a computer program. In order to build a computer model (model) for the entire power system, models of the components that make it up must be built, including the lines that are an essential component of the system. The theory of traveling waves on the lines is one of the most important techniques used in modeling lines that are suitable for studying transient operation conditions in electrical power systems.This paper aims to build an equivalent wave-line circuit based on the known partial differential equations of the line and to implement a developed algorithm and translate it into a computer program for modeling and simulating the waves traveling on the transmission line in order to study the transient states of the electrical power system. The research includes completing the mathematical model and algorithm, designing a computer program in the Matlab environment, making a practical application using it, and analyzing the calculation results. Notably, the completed algorithms and the designed and executed program are not available in the scientific publications. The research concludes with important and useful conclusions in the field of electrical network analysis in general and transient case analysis in particular.
Keywords: Computer Model for Electric Transmission Lines; Traveling Waves; Wave equivalent circuit; Wave storage; MATLAB Program